Viewing the hermit kingdom online : a multimodal critical discourse analysis of North Korean English-language news websites - Yeo, Marc Yi Fei (Nanyang Technological University, 2022)
Analysing propaganda websites controlled by North Korea is one of few avenues to understand this proverbial hermit kingdom. This study aims to uncover discourses that the North Korean regime communicates to international audiences through its propaganda websites, and how these discourses are communicated multimodally. A multimodal critical discourse analysis framework combining Halliday’s (1978) metafunctions with Machin (2012) and Machin and Mayr (2012)’s visual and linguistic devices in multimodal texts was used to examine the homepages of two North Korean government-controlled propaganda news websites, Rodong Sinmun and KCNA. Although the homepages are available in different languages, only English versions were analysed. The findings revealed that both homepages perpetuate discourses glorifying the regime, presenting mainly positive discourses about North Korea and capitalising on its ruling ideology, Juche. This served to legitimise many discourses, especially: i) Discourses praising Kim Jong-Un’s greatness and ii) the unity of North Koreans. Additionally, many discourses were constructed multimodally via a combination of images, text, layout, colour and/or typography. Therefore, this study proposes a possible framework for studying North Korea’s digital foreign propaganda strategies.